Rituals Around the Tombs of Wali: the Implementation of Islamic Shari’a of Demak and Kudus Communities - Mundakir, M. (LPPM IAIN Kudus, 2020)
View of life is a set of values which affects the entire life system of its adherents. One of the views of life among Demak and Kudus communities is the relationship between rituals conducted around the tomb and ukhrawi (eschatological) piety. Hence, these eschatological values are considered sacred, which are generated through activities and rituals integrated with Javanese culture and are held around the tomb. The tomb of Wali in Java coincide with the mosque and rituals outside the two epicenter are considered as worldly (profane) affairs. These various forms of ritual are part of Islamic shari’a embodiment of Demak and Kudus communities. For instance, the series of Grebeg Besar rituals are centered at Demak Great Mosque and Buka Luwur are centered at Menara Kudus Moque and Sunan Muria Mosque. Other forms of ritual are making pilgrimage to the tomb of Wali who are considered to have karamah and meditation through praying around the tomb to get blessings. By using the technique of grounded research, the socio-anthropological approach, this study succeeded in describing the implementation of Islamic shari’a in society which was formed from the life perspective of religious propragators (kiai). This study aims to reveal how the community’s views are formed which are manifested in the form of activities and rituals they believe to be a way of religion that will lead to the happiness of the ukhrawi life. The factors influencing the outlook on life and their characteristics are also the object of this study.